Neuroprotective Effect of Polyvalent Immunoglobulins on Mouse Models of Chemotherapy-Induced Peripheral Neuropathy - Mohamad Mroué; Flavien Bessaguet; Angélique Nizou; Laurence Richard; Franck Sturtz; Laurent Magy; Sylvie Bourthoumieu; Aurore Danigo; Claire Demiot (MDPI AG, 2024)
The occurrence of neuropathic pain in chemotherapy-induced peripheral neuropathy (CIPN) is a major dose-limiting effect of many commonly-used anticancer agents. Polyvalent human immunoglobulins (hIg), used in the treatment of several peripheral neuropathies, may alleviate neuropathic pain. The aim of this project was to investigate the preventive effect of hIg in two mouse models of CIPN, induced by vincristine (VCR, 100 µg/kg/d) and oxaliplatin (OXP, 6 mg/kg/3d). Human Ig were administered one day before the first injection of chemotherapy. The onset of CIPN and effects of hIg were assessed via functional tests and morphological analyses of sensory nerves. To evaluate the effect of hIg on chemotherapy cytotoxicity, viability assays were performed using hIg (0 to 12 mg/mL) combined with anticancer agents on human cancer cell lines. The preventive treatment with hIg alleviated tactile hypersensitivity and nerve injuries induced by VCR. It also alleviated tactile/cold hypersensitivities and nerve injuries induced by OXP. Treatment with hIg did not affect the cytotoxicity of either chemotherapy. Furthermore, in combination with VCR, hIg potentiated chemo-induced cell death. In conclusion, hIg is a promising therapy to prevent the onset of CIPN and potentiate chemotherapy effect on cancer, reinforcing the interest in hIg in the management of CIPN.